Efficient Parvovirus Replication Requires CRL4(Cdt2)-Targeted Depletion of p21 to Prevent Its Inhibitory Interaction with PCNA - Adeyemi, Richard O. (Public Library of Science, 2014)
Infection by the autonomous parvovirus minute virus of mice (MVM) induces a vigorous DNA damage response in host cells which it utilizes for its efficient replication. Although p53 remains activated, p21 protein levels remain low throughout the course of infection. We show here that efficient MVM replication required the targeting for degradation of p21 during this time by the CRL4(Cdt2) E3-ubiquitin ligase which became re-localized to MVM replication centers. PCNA provides a molecular platform for substrate recognition by the CRL4(Cdt2) E3-ubiquitin ligase and p21 targeting during MVM infection required its interaction both with Cdt2 and PCNA. PCNA is also an important co-factor for MVM replication which can be antagonized by p21 in vitro. Expression of a stable p21 mutant that retained interaction with PCNA inhibited MVM replication, while a stable p21 mutant which lacked this interaction did not. Thus, while interaction with PCNA was important for targeting p21 to the CRL4(Cdt2) ligase re-localized to MVM replication centers, efficient viral replication required subsequent depletion of p21 to abrogate its inhibition of PCNA.